Analisis Pemanfaatan Program Linear Untuk Alokasi Bahan Baku Dalam Rangka Memaksimalisasi Keuntungan: Studi Kasus Pada Perusahaan Asep Embordir Di Mangkubumi Tasikmalaya - Ayu Khoerun Nisa; Suci Putri Lestari; Barin Barlian (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The purpose of this study was to find out and analyze the calculation of the use of raw materials in Asep Embordir, the advantages of Asep Embordir before using the Linear Program and the advantages of Asep Embordir after using the Linear Program to increase maximum profit. The method used in this research is a survey method. With a descriptive analysis approach. The data used are data from interviews and direct observations during April 2022 regarding raw materials for making apparel, labor wage costs, and profits and production time. The existing problems are then formulated using the linear programming method and solved using the simplex method. The results showed that the use of raw materials in Rmfcollectionembroidery for cloth was 45 wood, buttons (27.8) packs, thread 9 rolls) and collar hardener (162 meters). The optimal production quantity for all production variations according to the company's production capacity is 540 pcs, while for KDLP the optimal production is 60 pcs. RMFCollectionembroidery profit from the selling price of Rp. 35,000/pcs, the total profit from KDLP is Rp. 2,100,000, this can be representative of the profit from the production of other clothing sizes. Based on the results of research studies, it is suggested that for the future, if asep border will increase the amount of production, companies need to take into account development costs and need to further analyze the use of all existing production capacity so that production can be carried out optimally.